2018
DOI: 10.2169/internalmedicine.9074-17
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Adrenocorticotropin Deficiency due to Nivolumab-induced Hypophysitis in a Patient with Advanced Lung Adenocarcinoma: A Case Report and Literature Review

Abstract: A 63-year-old Japanese woman with advanced lung adenocarcinoma developed isolated adrenocorticotropin deficiency caused by immune checkpoint inhibitor (ICI)-related hypophysitis following 8 months of nivolumab therapy. Prompt corticosteroid replacement therapy effectively relieved her secondary adrenal insufficiency symptoms and allowed her to pursue nivolumab therapy, which had been effective for the control of lung adenocarcinoma. Human leukocyte antigen (HLA) typing revealed the presence of the DRB1*04:05-D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 37 publications
2
27
0
Order By: Relevance
“…The present case promptly resulted in secondary adrenal insufficiency after transient ACTH elevation. In previous reports, most cases of ICI-induced hypophysitis were diagnosed based on adrenal insufficiency symptoms or hyponatremia with low ACTH and cortisol [5][6][7][8][9][10]. Only one case that resulted in secondary adrenal insufficiency after transient ACTH-dependent Cushing's syndrome was reported [11].…”
Section: Discussionmentioning
confidence: 99%
“…The present case promptly resulted in secondary adrenal insufficiency after transient ACTH elevation. In previous reports, most cases of ICI-induced hypophysitis were diagnosed based on adrenal insufficiency symptoms or hyponatremia with low ACTH and cortisol [5][6][7][8][9][10]. Only one case that resulted in secondary adrenal insufficiency after transient ACTH-dependent Cushing's syndrome was reported [11].…”
Section: Discussionmentioning
confidence: 99%
“…Deficiency of adrenocorticotropic hormone (ACTH) secretion is observed in almost all patients who develop hypopituitarism induced by ICIs [6]. While TSH and/or gonadotropin deficiency is often accompanied by ACTH deficiency in patients treated with anti-CTLA-4 antibodies, almost all patients who develop pituitary dysfunction with anti-PD-1 or anti-PD-L1 antibodies show isolated ACTH deficiency [15]. Central diabetes insipidus is rarely induced by ICIs [6].…”
Section: Overviewmentioning
confidence: 99%
“…Recently, immune‐checkpoint inhibitor (ICI) has been used for treatment of malignant tumours. As the use of ICI has increased, reported cases of ICI‐induced endocrine dysfunctions such as destructive thyroiditis, hypophysitis and type 1 diabetes have been increased . Anticytotoxic T lymphocyte antigen 4 (CTLA‐4) antibody induces hypophysitis, while cases of antiprogrammed cell death protein 1 (PD‐1) antibody‐induced IAD (PD1‐IAD) were reported .…”
Section: Introductionmentioning
confidence: 99%
“…As the use of ICI has increased, reported cases of ICI‐induced endocrine dysfunctions such as destructive thyroiditis, hypophysitis and type 1 diabetes have been increased . Anticytotoxic T lymphocyte antigen 4 (CTLA‐4) antibody induces hypophysitis, while cases of antiprogrammed cell death protein 1 (PD‐1) antibody‐induced IAD (PD1‐IAD) were reported . Faje et al reported that headaches, pituitary enlargement on MRI and multiple anterior pituitary hormone deficiencies would occur less commonly in anti‐PD‐1 antibody‐induced hypophysitis than in anti‐CTLA‐4 antibody‐induced hypophysitis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation